COORPORATE SOCIAL RESPONSIBILITY DALAM SUDUT PANDANG FIQIH HARTA DAN AKUNTANSI - Sri Suharti; Iwan Setiawan (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
Corporate social responsibility in the company law is a company obligation, which aims to increase the role of the private sector in economic development and equitable social welfare. However, until now, this goal has not been achieved, due to the company's reluctance to do so. This is reinforced from the results of previous research, that CSR is not correlated with an increase in company profits, even if donation activities are not related to company operations and profits, then these expenses cannot be recorded as an expense that reduces corporate taxes. This is different from the concept of CSR in the view of wealth fiqh, which places property as the property of Allah and must be used as much as possible for the benefit of all humans. This study aims to compare CSR in the view of wealth and accounting fiqh. This research uses literature review method using data sourced from books, journals / articles, reports and websites. The results of this study found that CSR in the view of wealth fiqh is permissible because there is no fatwa prohibiting it as long as the assets used do not come from business activities that are prohibited in Islam. There is a difference in the concept of assets according to fiqh, namely that assets cannot be stacked for personal gain and must be distributed to others, whereas according to the accounting concept, assets are accumulated and distributed to owners of capital.Key words: capital,  cooperate social responsibility, and fiqh of assets.